Environmental Effect of Bus Priority Measures Applied on a Road Network in Santiago, Chile. Issue 8 (December 2018) - Karekla, Xenia; Fernandez, Rodrigo; Tyler, Nick
Air pollution is at the highest levels ever and there is currently a worldwide initiative by transport engineers and urban planners to redesign public transport modes and cities to become more sustainable and environmentally friendly. The environmental impact of everyday activities is more apparent in developing cities which take longer to adapt to advanced methods of running public transport modes. This study aims to investigate the reduction of bus energy consumption and carbon emissions through bus priority measures in a bus route in the city of Santiago, Chile. Two bus priority schemes are tested in this study: Bus Only Lanes and Bus Signal Priority. The microscopic traffic simulator TSIS-CORSIM is used to quantify the environmental impact of these schemes. The results have shown that both schemes lead to lower fuel consumption and emissions, especially for the bus service. The environmental improvements are mostly apparent at traffic flows below 1000 veh/h, with clear benefits for both the bus service and passenger cars when dedicated bus lanes are included in the road infrastructure.